2017
DOI: 10.1515/rmzmag-2017-0004
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of Fluvial Sediments from Geregu, Southwest Nigeria

Abstract: Geochemical analysis of fluvial sediments on the banks of River Ero using inductively coupled plasma mass spectrometry illustrates their maturity, provenance and tectonic setting. The analysed sediment samples show low SiO 2 /Al 2 O 3 ratios of 2.92-2.99 (units FL_A, FL_B and FL_E) and high SiO 2 /Al 2 O 3 ratios of 4. FL_D, FL_F and FL_G). Sediments were geochemically classified as shales (units FL_A, FL_B and FL_E) and greywackes (units FL_C, FL_D, FL_F and FL_G). Ključne besede: rečni sedimenti, Eu anoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…Thus the friction factor is a function of Reynolds's number and independent of the penstock's material properties as implied by the equation (5). In laminar flow, according to the equation (5), the friction factor is inversely proportional to viscous energy losses.…”
Section: Head Losses In the Penstock Head Losses In The Penstock Headmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the friction factor is a function of Reynolds's number and independent of the penstock's material properties as implied by the equation (5). In laminar flow, according to the equation (5), the friction factor is inversely proportional to viscous energy losses.…”
Section: Head Losses In the Penstock Head Losses In The Penstock Headmentioning
confidence: 99%
“…It is located within the equatorial region with two climatic conditions -the wet and dry seasons [4]. The River Ethiope's volumetric flow has been investigated by Otuagoma et al [4] and the economic potentials of the river have also been reported on by Adiotomre et al [5]. Figure 1.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 98%
“…A-NdeMili River(Asowata, 2017) B-Nkisi River(Asowata, 2017) C-Akure stream sediments(Asowata et al, 2015) D-Geregu River sediments(Adiotomre, et al 2017) E-Lagos lagoon (Olatunji and Abimbola, 2010) F-Average Share Concentration(Turekian and Wedepohl, 1961) G-Southwest River Basin Sediments(Lapworth, et al, 2012) H-Lagos Coaster Stream Sediments(Odukoya and Akande, 2015) …”
mentioning
confidence: 99%